The Impact of Employees’ Recognition, Rewards and Job Stress on Job Performance: Mediating Role of Perceived Organization Support - Syed Durrab Hussain; Dr. Abdul Khaliq; Qasim Ali Nisar; Aamir Zamir Kamboh; Shahzad Ali (SEISENSE (PRIVATE) LIMITED, 2019)
Aim - the purpose of this study is to examine the role of employee rewards, recognition, and job-related stress towards employee performance considering the mediating role of perceived organizational support in the call-centers located in Lahore, Pakistan. Design - The data has been gathered through the survey method of the questionnaire. A simple random sampling technique is used for this study. Confirmatory factor analysis (CFA) and structure equation modeling (SEM) techniques have been used for statistical analysis. Findings - Results showed that employee rewards and recognition have a significant and positive effect on employee performance whereas job stress has a significant and negative effect on employee performance. Findings also revealed that perceived organizational support significantly and fully mediates the relationship between employee rewards, recognition, and job stress and employee performance. So this study puts light on crucial factors that lead to better employee performance. Implications - Employee rewards and recognition play an important role in overall employee performance. If the companies will not take it seriously, then it might lead to negative consequences. On the other hand, job stress also plays a vital role in employee performance.